Unveiling key e-learning ingredients for enhancing higher-order thinking skills - Piaw, Chua Yan; Ying, Loo Fung; Chiat, Loo Fung (Discover, 2025)
The existing e-learning models for higher-order thinking skills (HOTS) enhancement focus more on technology and e-learning methods, ignoring the important roles of human factors such as e-leadership, collaboration, and readiness. This exploratory sequential mixed-methods design study aimed to identify significant factors for e-learning practices that enhance HOTS. Semi-structured interviews were conducted with school administrators, teachers, students, parents, and school software experts, and the transcripts were analyzed using ATLAS.ti. Seven core factors emerged from the study: collaboration, readiness, e-leadership, personal factors, strategies, practices, and organizational factors. Their associations were verified through a quantitative survey involving 430 secondary school teachers. The quantitative data was analyzed using PLS-SEM and cIPMA in SMARTPLS 4, resulting in five sub-models defining a HOTS enhancement framework for schools e-learning. E-learning practices, strategies, collaboration, organizational factors, readiness, and e-leadership are six significant necessities for enhancing higher-order thinking skills (HOTS). Besides that, 41.302% of school leaders and teachers did not meet the minimum required level of e-leadership needed to achieve at least 80% HOTS enhancement in e-learning. This highlights the critical role of school leaders and teachers in leveraging e-leadership within e-learning platforms. This research provides a new model that educational leaders, policymakers, and educators can adopt to enhance HOTS in e-learning.